The Development of Pop Up 3D General Map Using Discovery Learning Models to Improve Creativity and Learning Outcomes of Social Studies Grade V Elementary School - Ningsih, Wahyu Kurnia; Riyanto, Yatim; Suyanto, Totok (Universitas Malikussaleh, 2019)
The researcher was interested in developing learning media